Kultura, edukacja i tożsamość mniejszości – przypadek palestyńskich Arabów w Izraelu - Izabel S., Ramadan (Studia Edukacyjne, 2017)
The purpose of this article is to address the links between minority culture, education and identity in the context of Palestinian Arabs in Israel (PAI). In an effort to demonstrate the unique socio-political status and cultural orientation of the PAI, the historical background of Palestinians in Israel is provided as well as a description of the educational system in Israel, with emphasis on Arab sector education. Against this background, I examine: (1) issues of education and identity among PAI and (2) the potential for identity conflict. Since the majority of teachers in the Arab sector are women, issues of gender relations are also discussed. The narrative methodology is recommended for further research on the way in which Palestinian Arab teachers, as potential agents of social change, relate to the broader cultural context in which they live and how identity issues are managed and expressed in the context of professional roles. The author of this article is a Palestinian Arab teacher in the Israeli educational system. This provides an opportunity for an in-depth analysis of the phenomena presented from an “insider” perspective.